The Use of Digital Folklore as a Medium for Teaching Indonesian to Instill Values in Elementary Schools - Slamet Slamet; Lilik Binti Mirnawati; Fajar Setiawan (Literasi Nusantara, 2026)
This study aims to describe the use of digital folklore media "Asal-Usul Surabaya" as an Indonesian learning medium for instilling values in elementary schools. This research uses a qualitative approach with a case study type. Data were collected through in-depth interviews using semi-structured interview guidelines, participant observation with observation sheets and field notes, and documentation studies. The data is analyzed interactively which includes the stages of data reduction, data presentation, and conclusion/verification. The results of the study show that: (1) Media implementation requires pedagogical adaptation of teachers and is supported by visionary school policies; (2) Media succeeds in increasing student engagement in a multimodal manner and functions as a common ground for learning; (3) Narrative understanding and internalization of students' character values increases, although there are technical and cognitive constraints that require improvement of media design. The discussion linked the findings to TPACK theory, cognitive theory of multimedia learning, and multimodal literacy, which confirmed that success is determined by the synergy between school policies, teachers' pedagogical competence, and inclusive media design principles. Digital folklore is an effective learning medium for elementary Indonesian. Its effectiveness is multifactorial, depending on the school's policy support, the teacher's ability to design and mediate learning, and the quality of the media design itself that takes into account the technical and cognitive aspects of the students. This study recommends a holistic approach in adopting similar media to ensure sustainability and optimal learning impact.